2017
DOI: 10.18632/oncotarget.15159
|View full text |Cite
|
Sign up to set email alerts
|

XIAP 3′-untranslated region as a ceRNA promotes FSCN1 function in inducing the progression of breast cancer by binding endogenous miR-29a-5p

Abstract: The non-coding 3′-untranslated region (UTR) of genes play an important role in the regulation of microRNA (miRNA) functions, since it can bind and inactivate multiple miRNAs. Herein, we report that ectopic expression of XIAP 3′UTR increased human breast cancer cells proliferation, colony formation, migration, invasion and xenograft tumor growth and suppressed tumor cell death. To investigate this process, we further correlated the genome-wide transcriptional profiling with the gene expression alterations after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…It has been reported that lncRNA DLX6-AS1 was up-regulated in lung adenocarcinoma (LAC) tissues compared to paired adjacent normal lung tissues and high DLX6-AS1 expression levels were significantly associated with both histological differentiation and TNM stage [41]. Recent researches have demonstrated that FSCN1, SOX11 and PSAT1 were associated with poor clinical outcome in breast cancer [42][43][44]. Our results are consistent with these reports.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that lncRNA DLX6-AS1 was up-regulated in lung adenocarcinoma (LAC) tissues compared to paired adjacent normal lung tissues and high DLX6-AS1 expression levels were significantly associated with both histological differentiation and TNM stage [41]. Recent researches have demonstrated that FSCN1, SOX11 and PSAT1 were associated with poor clinical outcome in breast cancer [42][43][44]. Our results are consistent with these reports.…”
Section: Discussionsupporting
confidence: 92%
“…miRNAs are reported to function through binding to 3’-untranslated region (3’UTR) of numerous target genes, resulting in degradation of mRNA or translation block [9, 10]. Mounting literatures have proved that miRNAs are involved in multiple diseases including MI [11-13].…”
Section: Introductionmentioning
confidence: 99%
“…XIAP, as a member of the inhibitors of apoptosis family, has been reported in numerous types of human cancer, and is associated with chemical or radiation resistance (27)(28)(29)(30). Recent studies indicated that expression of XIAP may be regulated by miRNAs (31)(32)(33)(34). In the current study, it was observed that XIAP is a direct target gene of miR-149 in ovarian cancer.…”
Section: Discussionmentioning
confidence: 54%